Revealing The Meaning of Émbu in Buying and Selling Transactions in Madura: A Phenomenological Study - Dewi, Ika Oktaviana; Setiawan, Nanang; Rohemah, Riskiyatur; Muria, Risky Mezi; Wahyudi, Imam (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2024)
This study aims to uncover the meaning behind the tradition of émbu in buying and selling transactions in Madura. The study employs a phenomenological approach focusing on the understanding and meanings attributed by the individuals involved. Data were gathered through participatory observation and in-depth interviews with émbu practitioners in several traditional markets in Madura. Émbu refers to the additional gift given by sellers to buyers after a transaction. The émbu tradition reflects trading ethics and strengthens social relationships among the Madurese community. The study findings indicate that the émbu tradition holds several significant meanings for the Madurese people. Émbu is seen as a symbol of appreciation, gratitude, efforts to maintain social harmony, and a marketing method. It helps foster customer loyalty and builds trust between sellers and buyers. Émbu enhances cultural solidarity and reinforces Madurese identity amidst economic globalization. This study contributes to strengthening the role of local wisdom in social and cultural values that influence economic practices in society. It underscores the importance of preserving local wisdom in the era of globalization as a form of cultural wealth worth preserving. The uniqueness of this research lies in uncovering the various complex dimensions of the émbu tradition, which have been underexplored in previous literature.